IONIC LIQUIDS FOR EXTRACTION OF B CAROTENE: MODELING AND EXPERIMENTAL APPROACHES - RAJABI, MANSOURE SADAT (2016)
Bcarotene, an important bio-molecule with highly unsaturated heavy structure (C4oHs6) is available in plenty of natural products. This hydrocarbon with noticeable antioxidant is a valuable compound in food and pharmaceutical industries. ~-carotene has been extracted from different sources using several techniques including super critical fluid extraction, ultrasound assisted extraction and traditional solvent extraction. However, these methods have several limitations. For instance, adverse operating conditions, extensively usage of VOCs and required special equipment. To overcome abovementioned issues, development of a novel method for ~-carotene extraction was considered. Recently, ionic liquids (ILs) - green and tailor made solvents - have been involved in bio-molecules extraction and shown to be efficient replacement for conventional solvents.